Poor Sleep in Community-Dwelling Polysubstance Users: Association With Khat Dependence, Metacognition, and Socio-Demographic Factors - Manzar, Md Dilshad; Alghadir, Ahmad H.; Khan, Masood; Salahuddin, Mohammed; Hassen, Hamid Yimam; Almansour, Ahmed M.; Nureye, Dejen; Tekalign, Eyob; Shah, Showkat Ahmad; Pandi-Perumal, Seithikurippu R.; Bahammam, Ahmed S. (Frontiers in Psychiatry, 2022)
Purpose Poor sleep and cognitive deficits are often associated with increased drug use. However, no study has addressed the relationship between poor sleep, substance dependence, and metacognitive deficit in polysubstance users. Methods This was a cross-sectional study with a simple random sampling involving community-dwelling polysubstance users (n = 326, age = 18–43 years) in Mizan, Ethiopia. Participants completed a brief sleep questionnaire, severity of dependence on khat (SDS-Khat), a brief meta-cognition questionnaire, and a socio-demographic survey. Results Majority (56.4%) of the polysubstance users had sleep disturbance. Chronic health conditions [adjusted odds ratio (AOR) = 2.52, 95% confidence interval (CI) 1.31–4.85], chronic conditions in the family (AOR = 2.69, 95% CI 1.40–5.20), illiterate-primary level of educational status (AOR = 2.40, 95% CI 1.30–4.04), higher SDS-Khat score (AOR = 1.39, 95% CI 1.13–1.72), and lower meta-cognition score (AOR = 0.90, 95% CI 0.84–0.97) predicted poor sleep in the polysubstance users. Moreover, low metacognition score and high SDS score also predicted additional sleep disturbances like chronic sleep insufficiency, lethargy and restlessness after nighttime sleep, socio-occupational dysfunctions, and daytime disturbances in polysubstance users. Conclusion Poor sleep, severe khat dependence, and metacognitive deficits are common in community polysubstance users. Moreover, poor sleep is associated with higher khat dependence, lower metacognitive ability, lower educational status, and the presence of chronic conditions in polysubstance users or their families.